Fieldwork in modern Chinese history
1 online resource.
Keywords: "This book explores how fieldwork has been used to research Chinese history in the past and new ways that others might use in it the future. It introduces the previous generations of scholars who ventured out of the archive to conduct local investigations in Chinese cities, villages, farms and temples. It goes on to present the techniques of historical fieldwork, providing guidance on how to integrate oral history into research plans and archival research, conduct interviews, and locate sources in the field. Chapters by established researchers relate these techniques to specific types of fieldwork, including religion, the imperial past, natural environments and agriculture. Combining the past and the future of the craft, the book provides a rich resource for scholars coming new to fieldwork in the history of China"--